TiO2–BiVO4 Heterostructure to Enhance Photoelectrochemical Efficiency for Sensitive Aptasensing - Liu, Pei Pei; Liu, Xiaoqiang; Huo, Xiao He; Tang, Yunfei; Xu, Jun; Ju, Huangxian (ACS applied materials & interfaces, 2017)
This work designed a nanocomposite to enhance the photoelectrochemical (PEC) efficiency by depositing BiVO4 nanoparticles on TiO2 nanospheres with a solvothermal method. The TiO2–BiVO4 heterostructure was characterized with various spectroscopic and microscopic techniques and was employed as a nanostructured support to cross-link DNA aptamer for constructing a visible-light driven PEC aptasensor. The TiO2 nanospheres provided a biocompatible microenvironment, and the high surface area of the heterostructure enhanced the loading of aptamer molecules. The small energy gap of BiVO4 improved the PEC property of the nanocomposite compared with the pure TiO2 under visible-light irradiation. The advantages of the nanocomposite along with the high loading of recognition molecules greatly improved the sensitivity of the aptasensor. Using 17β-estradiol as an analyst model, the proposed PEC biosensor showed excellent analytical performance with high sensitivity, low detection limit of 0.022 pM, and high selectivity in a detectable concentration range of 0.1–250 pM, indicating the promising application of the designed TiO2–BiVO4 heterostructure in PEC biosensing.